2005
DOI: 10.1055/s-2005-919719
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Type I and Type III Injectable Human Collagen for Dermal Fill: 10 Years of Clinical Experience in China

Abstract: This article reports preclinical and clinical experience with a type I and type III injectable human collagen product derived from human sources (containing type I and type III collagen in a proportion of 44:56) utilized as a dermal filler. The preclinical study involves experiments characterizing the histological changes observed after type I and type III injectable human collagen injection in rats. The clinical trial is a study of 123 patients treated with type I and type III injectable human collagen for pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, there is a very high interspecies homology of collagens so that the results can be transferred very well [ 58 ]. In addition, no adverse or immune reactions have been reported in human clinical trials with injected collagen I and III [ 59 ]. Only an unspecific background reaction with rather low MFI-values without significant immunization patterns were found in both untreated and treated animals, when the sera of the rats were tested for anti-human HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a very high interspecies homology of collagens so that the results can be transferred very well [ 58 ]. In addition, no adverse or immune reactions have been reported in human clinical trials with injected collagen I and III [ 59 ]. Only an unspecific background reaction with rather low MFI-values without significant immunization patterns were found in both untreated and treated animals, when the sera of the rats were tested for anti-human HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These allergic reactions are believed to be an immunological response to bovine collagen. 39 Additionally, the Centers for Disease Control and Prevention and the FDA both concluded that a significant statistical association exists between bovine collagen used in dermal fillers and dermatomyositis. 40 Autologous and cadaveric human collagens have a lower risk of hypersensitivity, but possess the risk of disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate correction of dermal defects and stimulation of new tissue generation by slowly degradable soft tissue fillers is ideal for dermal fillers. 37 In this study, DiHMs (pH 5 and 7) induced a gradual increase in collagen deposition and neovascularization. The thickness of fibroconnective tissue, the degree of neovascularization and infiltration of macrophages, and giant cells, increased gradually with time in the DiHM implants.…”
Section: Discussionmentioning
confidence: 52%
“…Immediate correction of dermal defects and stimulation of new tissue generation by slowly degradable soft tissue fillers is ideal for dermal fillers . In this study, DiHMs (pH 5 and 7) induced a gradual increase in collagen deposition and neovascularization.…”
Section: Discussionmentioning
confidence: 99%